ECG markers of positive drug challenge with ajmaline in patients with Brugada syndrome - Tueluemen, Erol; Kruska, Mathieu; Würfel, Sara; Kohl, Maximilian; Liebe, Volker; Akın, Ibrahim; Kuschyk, Jürgen; Dürschmied, Daniel; Borggrefe, Martin; Rudic, Boris (Annals of noninvasive electrocardiology, 2026)
Background Ajmaline challenge (AC) is used for diagnosing suspected Brugada syndrome (BS) in patients with unexplained syncope, survived cardiac arrest, or for family screening. Purpose To evaluate baseline ECG markers predicting a positive AC in the absence of a spontaneous diagnostic Brugada ECG. Methods Baseline ECGs of 221 consecutive patients undergoing AC (up to 1 mg/kg bodyweight) were analyzed. ECGs from positive and negative tests were compared, with Q-, R-, S-, J-, and T-wave amplitudes and intervals measured in all 12 leads. Results 221 patients underwent AC; the cohort was 71% male, and 7% had survived cardiac arrest. AC was positive in 93 patients (42%). Prominent S-waves in lead II and J-waves in V1 predicted a positive AC (S-wave duration: 36 vs. 22 ms, p < 0.01; J-wave amplitude V1: 0.06 vs. 0.01 mV, p < 0.001). ROC analysis confirmed discriminative value for S-wave duration in lead II (AUC 0.79) and J-wave amplitude in V1 (AUC 0.71). A cut off of ≥ 19 ms for S-wave duration in lead II showed 96% sensitivity for a positive test (OR 17.3, p < 0.001). J-wave amplitude in V1 ≥ 0.05 mV was also significantly associated (OR 5.4, p < 0.001). Conclusion In patients without a spontaneous diagnostic Brugada ECG, prominent S-waves in lead II and J-waves in V1 are subtle electrical abnormalities that help identify patients and family members with a higher likelihood of positive AC.
Erstmals veröffentlicht: 8. Dezember 2025
Gesehen am 26.01.2026